The Influence of Islamic Digital Content on Political Participation Among Muslim Millennials in Medan City - Ahmad Fajar Bahri Harahap; Rubino Rubino; Erwan Effendi (Universitas Nurul Jadid, 2024)
This study aims to determine the influence of Islamic digital content on the political participation of Muslim millennials in Medan and the factors that influence this influence, as well as to provide insight into the dynamics of politics among the young generation of Muslims. The research method used is qualitative, with data collection techniques including interviews and Focus Group Discussions (FGD). Primary data was obtained directly from respondents who are Muslim millennials in Medan, while secondary data came from various relevant literature. The research design applied was a case study with a focus on Medan. Based on the results of the study, Islamic digital content plays a significant role in increasing the political participation of Muslim millennials in Medan. Muslim millennials become more sensitive to political issues after being exposed to digital content that discusses political and social aspects from an Islamic perspective. Content that emphasizes social justice, fair leadership, and participation in elections encourages them to be more active in politics, seeing it as part of the Islamic values that they uphold. Religious figures and Muslim influencers on social media play a significant role in conveying political messages wrapped in religious values. Social media also facilitates access to political information, informing Muslim millennials about current issues. It is critical to ensure that the content disseminated is accurate, unbiased, and supports healthy democratic values